Asylum Determination in Europe Ethnographic Perspectives - Gill, Nick; Good, Anthony (Palgrave Socio-Legal Studies, 2019)
Drawing on new research material from ten European countries, Asylum Determination in Europe: Ethnographic Perspectives brings together a range of detailed accounts of the legal and bureaucratic processes by which asylum claims are decided.The book includes a legal overview of European asylum determination procedures, followed by sections on the diverse actors involved, the means by which they communicate, and the ways in which they make life and death decisions on a daily basis. It offers a contextually rich account that moves beyond doctrinal law to uncover the gaps and variances between formal policy and legislation, and law as actually practiced. The contributors employ a variety of disciplinary perspectives - sociological, anthropological, geographical and linguistic - but are united in their use of an ethnographic methodological approach. Through this lens, the book captures the confusion, improvisation, inconsistency, complexity and emotional turmoil inherent to the process of claiming asylum in Europe.